Ethnobotanical Survey on the Plants Used in the Control of Nematodes in the Zone of Niayes of Thies/Senegal - El Hadji Gorgui Diouf; Doudou Diop; Abdoulaye Gueye; Talibouya Ndior; Mamadou Latyr Ndour; Adama Faye; Mamadou (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Crop losses in vegetable crops due to nematodes are a concern in a country like Senegal where food demand is increasingly high. The use of chemical pesticides has made great progress in increasing harvests in Senegal. But these pesticides have negative effects on the environment and on human health. Crops are often contaminated as well as groundwater. The use of natural products to remedy this phenomenon is very important, especially in areas such as the Niayes zone where the climate and soil are very favorable for market gardening and where water contamination is very sensitive. The aim of our study is to identify the plants used to control nematodes in the Niayes area of This. To this end, we conducted an ethnobotanical survey of 100 people of different ages and sexes in this area. The results showed 17 plant species used to control nematodes in 12 families. Among these species, the most cited were Azadirachta indica A. Juss. Juss, Calotropis procera (Ait.) F. and Cassia Occidentalis L. Leaves (71%) are mostly used. The sample is often dried and ground (45%) or fresh (case of hydrodistillation) (53%) before preparation. Water (92%) is the most used solvent for extraction. Maceration (85%) and infusion are the most common preparation methods. The application of these preparations by systemic action (94%) is more adopted than fumigation. Local people find these preparations rather effective (78%), which is very encouraging. The present study constitutes a database for further studies in the field of Senegalese pharmacopeia. In addition, scientific research on bionematicidal substances may be conducted in the future to evaluate the effectiveness of these plants identified in the Niayes area of This for the protection of vegetable crops against nematodes.